Catholic Religious and Spiritual Identity of Mediterranean Adolescents: Comparing Four Regions in Post-Communist and Western Europe - Živković, Ilija (Array, 2008)
We investigated religious identity and spiritual profile of adolescents in selected communities of Bosnia, Croatia, Italy and Spain using a standardized questionnaire on three major areas of interest: inner content of religiosity, attitude towards Catholic doctrine and regulations, and the impact of religiosity on daily life. Controlling sample differences by age, socioeconomic status and gender, we tested the significance of differences in attitudes of adolescents in transitional post- Communist societies (rural and small-town Croatia and Bosnia) and western European postmodern culture (Sicily in Italy and Mallorca and Madrid in Spain) by analysis of variance (ANOVA). We tested 1204 adolescents from Franciscan high schools (Sicily and Spain) and public high schools (Bosnia and Croatia). Overall, Spanish youngsters appeared least religious and most socially permissive as they differed significantly from other groups in all three major areas of interest. Bosnian and Croatian adolescents were similar to each other and overall more religiously imbued. Sicilians were most often found between Spaniards on one side and Croatians on the other. The study shows a gradient of increasing religiosity from the West to the East, from Spain to Bosnia and establishes baseline values for the future longitudinal studies of the communities in Bosnia and Croatia.